Modernization and Regionalization of China as Factors of Globalization: a Philosophical and Comparative Analysis of Chinese Studies - Dmitry Viktorovich, Sukharev; Chuanming, Zhou; Olga Andreevna, Borisenko (International Journal of Psychosocial Rehabilitation, 2019)
This article presents a philosophical analysis of the work of Chinese scientists who study the processes of modernization and regionalization in China. The purpose of the study: to justify that the modernization and regionalization of China as globalization processes have conceptual and theoretical foundations that are purposefully formed in Chinese scientific thought. The authors used the following methodology to realize the goal of the study: the method of social constructionism, comparative approach, method of interpretation, systemic method, integrative approach. The analysis showed that in the studies of Chinese scientists the rationale for regionalization and modernization as a factor in globalization processes prevails. The authors emphasized that the processes of modernization and regionalization are considered by Chinese scientists in the system. The authors present the system in the following version: analysis of foreign experience - formation of a national theory - verification of a theory in practice - preparation of a concept - analysis of practical results. This, according to the authors, reveals the meaning of the study: Chinese scientists through the scientific sphere form an idea that confirms the national policy of the state.